2017
DOI: 10.3892/ijmm.2017.3162
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidins inhibit the proliferation, migration and invasion of tongue squamous cell carcinoma cells through suppressing the protein kinase?B/nuclear factor-κB signaling pathway

Abstract: Tongue squamous cell carcinoma (TSCC) is the most common oral squamous cell carcinoma. Despite significant advances in combined therapies, the 5-year survival rate of patients with TSCC has not notably improved; this is due to regional recurrences and lymph node metastasis. Grape seed proanthocyanidins (GSPs) are consumed as dietary supplements worldwide and possess anticancer activity against several different types of cancer. However, their effect on TSCC and the underlying mechanisms by which they function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…28 GSPs were reported to significantly suppress the migratory and invasive ability of tongue squamous cell carcinoma (TSCC) cells through blocking the secretion of matrix metalloproteinases. 29 Similarly, the experiment of in vivo bioluminescence imaging showed that dietary administration of GSPs could suppress the migration of intravenously injected melanoma cells through the activation of β-catenin and its downstream targets in the lungs of immune-compromised nude mice. 30 In our results, the reduction of SiHa and HeLa cells migration and invasion in our study indicated that the treatment of PC could also markedly inhibit the metastasis progression of CC by controlling tumor cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…28 GSPs were reported to significantly suppress the migratory and invasive ability of tongue squamous cell carcinoma (TSCC) cells through blocking the secretion of matrix metalloproteinases. 29 Similarly, the experiment of in vivo bioluminescence imaging showed that dietary administration of GSPs could suppress the migration of intravenously injected melanoma cells through the activation of β-catenin and its downstream targets in the lungs of immune-compromised nude mice. 30 In our results, the reduction of SiHa and HeLa cells migration and invasion in our study indicated that the treatment of PC could also markedly inhibit the metastasis progression of CC by controlling tumor cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Tongue squamous cell carcinoma (TSCC), the most common malignant tumor of the oral region, is well known for its high rate of lymph node metastasis and poor prognosis [1,2]. Currently, combination chemotherapy based on cisplatin (cis-diamminedichloroplatinum II, CDDP) is the standard treatment for many types of cancers, including TSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (66) reported that c-MYC is likely to drive TSCC progression while Huang et al (67) demonstrated that Iroquois homeobox gene 5 can promote the aggressiveness of TSCC cells by activating the NF-κB signaling pathway, leading to an increase in the nuclear p65 levels and IκBα degradation. In addition, grape seed proanthocyanidin markedly repressed the activity of NF-κB and promoted apoptosis of TSCC cells by regulating the stability and activity of Bax and downgrading the Bcl-2 and Bcl-xL proteins, and additionally suppressed the aggressiveness and metastasis of TSCC cells by restraining the secretion of MMP-2 and MMP-9 in the cells (68). A previous study reported that isobavachalcone may inhibit the expression of the apoptosis-related protein Bcl-2 (69).…”
Section: Discussionmentioning
confidence: 98%